PENGARUH DUKUNGAN KELUARGA TERHADAP EFIKASI DIRI PASIEN PPOK DI POLIKLINIK PARU RSUD KOJA JAKARTA UTARA - Dasuki, Dasuki (Jurnal Ilmiah Keperawatan, 2018)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease that cause of decreasing daily routine activities, that is why family support is essentially needed to increase self efficacy. The purpose of this research was to identify the significance of family support toward self efficacy of CPOD patients at pulmonary department of Koja public hospital in North Jakarta. Design used in this study was cross sectional. The populations were all COPD patients treating at pulmonary department of Koja public hospital in North Jakarta. Meanwhile, there were 70 samples used as respondents selected as accidental sampling based on inclusive and exclusive criteria. Data collected through administering questionnaire. Then, data were analyzed by using chi square test. The result of univariate analysis showed that majority of respondents were 42 elderlies (60%), 53 males (75.7%), and 54 jobless or retired people (77.1%). Whereas bivariate analysis revealed that there was a significance of family support regarding self efficacy (p value:0.000, α: 0,05). Chronic obstructive pulmonary disease is a chronic disease that cause limited physical ability to do daily routine activities, consequently family support play important role for patients in increasing self efficacy. Key words : Family support, Self efficacy, COPD